A triblock terpolymer vs. blends of diblock copolymers for nanocapsules addressed by three independent stimuli. Issue 20 (27th April 2016) - Behzadi, Shahed; Gallei, Markus; Elbert, Johannes; Appold, Michael; Glasser, Gunnar; Landfester, Katharina; Crespy, Daniel
Abstract : The chemical structure of triblock terpolymers is exploited to achieve polymer nanocapsules responsive to three different stimuli. Abstract : Stimuli-responsive micro- to nano-scale containers have gained increasing attention due to their unique potential to selectively release payloads under specific environmental conditions. We report here novel triple stimuli-responsive nanocapsules that selectively respond to changes in temperature, pH value, and redox potential. The nanocapsules were prepared from either a triple responsive triblock terpolymer or a blend of responsive diblock copolymers, both synthesized by sequential anionic polymerization. We then compared the release performance of nanocapsules under oxidative conditions and changes of temperature or pH value. Our results reveal the close correlation between the release properties of stimuli-responsive nanocontainers and the microstructure of the polymer shell. In fact, the microphase separation between the responsive diblock copolymers across the shell significantly hinders the triggered release of the payload from the nanocapsules. These results demonstrate that the fine morphology of triblock terpolymers can be exploited to achieve the triggered release of payloads from polymer nanocontainers upon application of three different external triggers.